Pengaruh Online Customer Review, Citra Merek dan Religiusitas Terhadap Keputusan Pembelian Dengan Kepercayaan Konsumen Sebagai Variabel Intervening (Studi Pada Pengguna Marketplace Shopee Generasi Z) - Umma, Naritsul; Nabila, Rifda (Institut Agama Islam Negeri Madura, 2023)
The purpose of this study was to determine the effect of online customer reviews, brand image and religiosity on purchasing decisions with consumer trust as an intervening variable (a case study of Generation Z Market Place Shopee ). This research is a quantitative study using primary data with a population of Generation Z Shopee . The sampling technique used non-probability sampling with a purposive sampling method total of 100 respondents.The data was processed using SPSS for windows 25, the analytical method used the instrument test, classical assumption test, Sobel test and path analysis. Research results: 1) online customer reviews have no effect on purchasing decisions, 2) brand image has no effect on purchasing decisions, 3) religiosity hasa positive effect on purchasing decisions, 4) consumer trust has positive effect on purchasing decisions, 5) online customer reviews have no effect on consumer trust, 6) brand image has positive effect on consumer trust, 7) religiosity has positive effect on consumer trust, 8) consumer trust cannot mediate online customer reviews on purchasing decisions, 9) consumer trust can mediate brand image on purchasing decisions, 10 ) consumer confidence can mediate religiosity on purchasing decisions.